More than medications: a patient-centered assessment of Parkinson’s disease care needs during hospitalization - Shurer, Jessica; Golden, Shannon L. S.; Mihas, Paul; Browner, Nina (Frontiers in Aging Neuroscience, 2023)
Background Parkinson’s disease (PD) increases the risk of hospitalization and complications while in the hospital. Patient-centered care emphasizes active participation of patients in decision-making and has been found to improve satisfaction with care. Engaging in discussion and capturing hospitalization experience of a person with PD (PwP) and their family care partner (CP) is a critical step toward the development of quality improvement initiatives tailored to the unique hospitalization needs of PD population. Objectives This qualitative study aimed to identify the challenges and opportunities for PD patient-centered care in hospital setting. Methods Focus groups were held with PwPs and CPs to capture first-hand perspectives and generate consensus themes on PD care during hospitalization. A semi-structured guide for focus group discussions included questions about inpatient experiences and interactions with the health system and the clinical team. The data were analyzed using inductive thematic analysis. Results A total of 12 PwPs and 13 CPs participated in seven focus groups. Participants were 52% female and 28% non-white; 84% discussed unplanned hospitalizations. This paper focuses on two specific categories that emerged from the data analysis. The first category explored the impact of PD diagnosis on the hospital experience, specifically during planned and unplanned hospitalizations. The second category delves into the unique needs of PwPs and CPs during hospitalization, which included the importance of proper PD medication management, the need for improved hospital ambulation protocols, and the creation of disability informed hospital environment specific for PD. Conclusion PD diagnosis impacts the care experience, regardless of the reason for hospitalization. While provision of PD medications was a challenge during hospitalization, participants also desired flexibility in ambulation protocols and an environment that accommodated their disability. These findings highlight the importance of integrating the perspectives of PwPs and CPs when targeting patient-centered interventions to improve hospital experiences and outcomes.